Poetic Devices, Thematic Significance and Social Realities in Poetry: A Critical Literature Review - Arcilla Jr., Felix E. (RIRAI Publisher, 2024)
This study critically synthesized the existing scholarly research on poetic devices, thematic significance, and social realities. The researcher used a critical literature review and content analysis to scrutinize scientific literature. Based on the review, this study bridges the gap between poetic form and societal critique, highlighting poetry's capacity for thematic depth and social analysis. The artful use of metaphors, personification, imagery, etc., empowers poets to address complex socio-political narratives within their work, positioning poetry as a mirror of society’s multifaceted issues. Poets from varied cultures have historically harnessed verse to reflect on universal themes such as mortality, justice, and human experiences, affirming poetry's role as both a narrative force and a societal barometer. Furthermore, poetry's archival value as a historical record is illuminated, capturing the spirit of different ages and contributing to our collective societal understanding. Through this synthesis, poetry is recognized as an enduring vehicle for exploring and challenging social dynamics, immortalizing the collective human psyche in rhythmic form. Through their craft, poets offer critiques and engage in the socio-political commentary that continues to shape the literary canon and our collective understanding. The study's findings underscore poetry’s timeless relevance as a medium for social critique and thematic exploration